THE METHOD SIMULATING NON-STATIONARY FIELDS OF ATMOSPHERIC POLLUTANT CONCENTRATIONS - И. К. Васильева; А. С. Нечаусов (Радіоелектронні і комп'ютерні системи, 2016)
The calculational techniques of the pollutants concentration in the atmosphere have been considered. The probabilistic model based on the normal distribution as well as the SL-Johnson’s distribution has been proposed, which allows to consider non-steady nature of the factors which are shaping concentrations field. The developed model takes into account the spatial localization of the pollutant sources, the sources’ attributes that characterize the physical conditions of pollutants emission into the atmosphere, wind speed and direction, atmospheric diffusion and duration of the emission. The results of the simulation of atmospheric pollutants concentration fields for steadily and intermittently functioning point source of contamination in unstable weather conditions have been presented.